Motivasi Kerja Sebagai Mediator: Beban Kerja dan Stres Kerja Terhadap Produktivitas Kerja - Risma Yulianti; Erni Yuningsih; Tini Kartini (Pusat Riset dan Inovasi Nasional, 2025)
Low work productivity is still a major problem in many organizations, which is often caused by high workloads, increased work stres , and suboptimal work motivation. This problem has a direct impact on achieving organizational goals because productivity reflects the efficiency and effectiveness of human resources. This research aims to analyze the influence of workload, work stres , and work motivation on work productivity, both directly and indirectly. The research method used a quantitative approach with a descriptive verification design and involved 109 respondents. Data analysis was carried out using the Path Analysis method. The research results show that workload and work stres have a negative and significant effect on work motivation and work productivity, both directly and indirectly. Meanwhile, work motivation has a positive and significant influence on work productivity. These findings confirm that effective management of work load and stres as well as increasing work motivation are very important in overcoming employee productivity problems.